Bcl‐xL as prognostic marker and potential therapeutic target in cholangiocarcinoma. (14th September 2022) - Hoffmeister‐Wittmann, Paula; Mock, Andreas; Nichetti, Federico; Korell, Felix; Heilig, Christoph E.; Scherr, Anna‐Lena; Günther, Michael; Albrecht, Thomas; Kelmendi, Eblina; Xu, Kaiyu; Nader, Luisa; Kessler, Annika; et al.
Abstract: Intrahepatic, perihilar, and distal cholangiocarcinoma (iCCA, pCCA, dCCA) are highly malignant tumours with increasing mortality rates due to therapy resistances. Among the mechanisms mediating resistance, overexpression of anti‐apoptotic Bcl‐2 proteins (Bcl‐2, Bcl‐xL, Mcl‐1) is particularly important. In this study, we investigated whether antiapoptotic protein patterns are prognostically relevant and potential therapeutic targets in CCA. Bcl‐2 proteins were analysed in a pan‐cancer cohort from the NCT/DKFZ/DKTK MASTER registry trial ( n  = 1140, CCA n  = 72) via RNA‐sequencing and transcriptome‐based protein activity interference revealing high ranks of CCA for Bcl‐xL and Mcl‐1. Expression of Bcl‐xL, Mcl‐1, and Bcl‐2 was assessed in human CCA tissue and cell lines compared with cholangiocytes by immunohistochemistry, immunoblotting, and quantitative‐RT‐PCR. Immunohistochemistry confirmed the upregulation of Bcl‐xL and Mcl‐1 in iCCA tissues. Cell death of CCA cell lines upon treatment with specific small molecule inhibitors of Bcl‐xL (Wehi‐539), of Mcl‐1 (S63845), and Bcl‐2 (ABT‐199), either alone, in combination with each other or together with chemotherapeutics was assessed by flow cytometry. Targeting Bcl‐xL induced cell death and augmented the effect of chemotherapy in CCA cells. Combined inhibition of Bcl‐xL and Mcl‐1 led to a synergistic increase in cell death in CCA cell lines. Correlation between Bcl‐2 protein expression and survival was analysed within three independent patient cohorts from cancer centers in Germany comprising 656 CCA cases indicating a prognostic value of Bcl‐xL in CCA depending on the CCA subtype. Collectively, these observations identify Bcl‐xL as a key protein in cell death resistance of CCA and may pave the way for clinical application.